Concordance of Peripheral Blood and Bone Marrow Next-Generation Sequencing in Hematologic Neoplasms. (26th March 2022) - Jumniensuk, Chayanit; Nobori, Alexander; Lee, Thomas; Senaratne, T. Niroshi; Rao, Dinesh; Pullarkat, Sheeja
Abstract : Objective . Mutational analysis by next-generation sequencing (NGS) obtained by peripheral blood NGS has been of clinical interest to use as a minimally invasive screening tool. Our study evaluates the correlation between NGS results on peripheral blood and bone marrow in hematolymphoid disease. Method . We evaluated patients who had NGS for presumed hematologic malignancy performed on peripheral blood and bone marrow within a 1-year interval of each other. We excluded cases in which chemotherapy or bone marrow transplant occurred in the interval between the two tests. The concordance across peripheral blood and bone marrow NGS results was assessed by kappa coefficient analysis. Results . A total of 163 patients were studied. Concordance of peripheral blood and bone marrow NGS found in 150 patients (92.0%) with a kappa coefficient of 0.794 (kappa standard error 0.054) and P value for testing kappa <0.0001. Myeloid neoplasms showed concordant results in 77/78 cases (98.7%) with a kappa coefficient of 0.916. Lymphoid neoplasms showed concordant results in 26/31 cases (83.9%) with a kappa coefficient of 0.599. Nonneoplastic cases showed concordant results in 47/54 cases (87.0%) with a kappa coefficient of 0.743. Conclusion . Peripheral blood NGS is a reliable tool for mutational analysis and provides a less invasive method for screening and monitoring of the molecular profile.